The utility of De Ritis Ratio in predicting prognosis in testicular cancer - Guner, Ekrem; Seker, Kamil Gokhan; Arikan, Yusuf; Huseynov, Coshgun; Sam, Emre; Ozdal, Ozdem Levent (Aktuelle Urologie, 2020)
Objective We aimed to investigate the possible association between testicular cancer prognosis and De Ritis ratio (AST/ALT).Methods The medical records of all patients who underwent radical inguinal orchiectomy at a single tertiary in Istanbul, Turkey between 2006 and 2017 were retrospectively analyzed. Investigated parameters included patients’ demographics, complete blood count and blood biochemistry results, pathology results, treatment schemes, imaging results, and survival. De Ritis ratio was calculated as follows: AST/ALT.Results A total of 171 patients with a mean age of 32.6 ± 10.1 years were included in the study. 73 patients had T1, 83 had T2, 13 had T3 and 2 had T4 disease. Rete testis invasion was detected in 74 patients (43.3 %) as well as lymphovascular invasion in 93 (54.4 %) and tunica albuginea invasion in 80 (46.8 %) patients. The cut-off value for AST/ALT was set at 1.35 [Area Under Curve (AUC): 0.791 with a sensitivity of 80 % and specificity of 73 %]. No statistically significance was observed between patients with and without elevated AST/ALT according to rete testis invasion, lymphovascular invasion, tunica albuginea invasion, and tunica vaginalis invasion (p = .25, p = .63, p = 1.0 and p = 1.0, respectively). 28.2 % of patients with seminoma had AST/ALT > 1.35 however 41.9 % of patients with non-seminoma pathology had AST/ALT > 1.35 (p = .078). Mean estimated survival time of patients with AST/ALT > 1.35 was higher than those with AST/ALT < 1.35, 91.8 versus 70.4 months, p < .001). As seen in Kaplan-Meier analysis elevated AST/ALT is associated with early-term mortality.Conclusion De Ritis ratio was shown to be significantly associated with unfavorable prognosis. De Ritis ratio might serve as a prognostic biomarker in testicular tumor besides well-known tumor markers such as beta-human chorionic gonadotropin (hCG), alpha-fetoprotein (AFP) and lactate dehydrogenase (LDH).
Keywords: aspartate transaminase; alanine transaminase; testicular cancer; De Ritis Ratio